Basic, Excitement and Performance Factor of Customer Satisfaction in Malaysian Banks - Lye, Kim Soon (2012)
As customer satisfaction could lead to higher level of loyalty and profitability, many organizations such as banks have strategy level initiatives to assess and manage attributes that lead to higher overall customer satisfaction. The problem is past studies in customer satisfaction research have always assumed a linear relationship whereby performance of some service or product attributes may directly affect overall customer satisfaction. However, several recent researches are suggesting that the existence of a non-linear and asymmetric response of satisfaction to attribute level performance could lead to the misallocation of resources by organizations. This study aims to examine the service quality and service feature attributes of Malaysian bank customer satisfaction to reveal the presence of the factor structure. It has been argued that service determinants impact overall customer's satisfaction differently according to the predominant characteristics such as basic factors, exciting factors and performance factors. To further incorporate the complexity of their non-linear and asymmetric nature, the study will also examine relationship between individual attribute performance and overall customer satisfaction. The primary research methodology of this study will be based on a quantitative method of multiple regression using dummy variables. A convergence test will be conducted using the qualitative method of critical incident technique. The result of this study indicates that customer satisfaction consists of performance. basic and exciting factors which have different impact of satisfaction/dissatisfaction depending on their performance level. There are supports to the findings using the qualitative methods although for some attributes the classification differs. as there are limitations to the methodology. In addition to the different characteristics of the factor. The study also shows some support that resources will be misallocated, if these factors were analyzed using the traditional linear model of importance performance analysis.